UPAYA MENINGKATKAN PRESTASI BELAJAR SISWA DALAM MENYELESAIKAN PEMBAGIAN SUKU BANYAK DENGAN METODE PEMBAGIAN SINTETIK DI KELAS XI IPA SEMESTER IV TAMAN MADYA (SMA) TAMANSISWA MEDAN T.P 2009/2010 - Marzuki Ahmad (Institut Pendidikan Tapanuli Selatan, 2016)
This study aims to determine how the efforts made to improve student achievement by using synthetic division in sub subject of many ethnic division in grade XI Taman Madya (SMA) Tamansiswa Medan, in the academic year 2009/2010. The learning method applied in this research is the method of Synthetic Division with grooves Classroom Action Research (CAR), which is composed of two cycles. The subjects were all students of class XI Science Park Madya (SMA) Tamansiswa Medan Year 2009/2010 which amounted to 33 students and the object of research is the result of learning mathematics class XI IPA Taman Madya (SMA) Tamansiswa Medan in learning mathematics pambelajaran year 2009 / 2010. Instruments used in this research is to test and observation sheet. Data collected through the test description totaling 10 questions, which before has been tested to a test of validity, reliability and level of distress so that the instrument fit for use as a research instrument. The collection of data through observation is based indicators compiled students' communication skills in the activities undertaken pemberlajaran 2 meetings.Results showed learning synthetic division method can improve students' mathematics achievement in the subject sub division of polynomials in class XI. The increase in mathematics achievement in terms of the average value of 54.33 after the student initially apply action (first cycle) the average value of students increased to 68.03 and continued administration of the action (second cycle) the average value of students increased to 79, 42. So is the percentage of the value of mastery learning students from the beginning (preliminary data) students ketuntasannya 21.21% after the action on the test applied first cycle increased to 69.69% and the test cycle II increased to 87.87%. This study was used was successful because in classical learning completeness students has reached 80%. This shows that the application of the method of synthetic division on the subject of sub division of polynomials can improve student achievement, and can be used as an alternative to increase the attention and interest of students in learning division of polynomials.